PERANAN SEGMENTASI DALAM PERILAKU KONSUMEN GUNA MENCIPTAKAN IKLAN YANG EFEKTIF - Ambar - Lukitaningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2013)
ABSTRACT In life, many found the form of messages from producers to consumers is one form of advertising. Advertising is a form of information products and services from producers to consumers as well as delivery of messages through a media sponsor. Advertising in the marketing function is motivated by the need to strengthen and consumers need of a product to achieve compliance satisfaction. For it is necessary to create an effective ad to the right with the objectives to be achieved. In creating effective ads need to pay attention to consumer behavior to target, with an understanding of consumer behavior will improve the ability of marketers to compete with other similar products. Characteristics consumer advertisers should know, because the purpose of the advertising itself to persuade consumers to buy a product or service. In addition to the selection of the consumer characteristics specific market (segmentation) will be easier to communicate the product through advertising media. Or character traits in a group is a market segment data to facilitate market the product. By doing market segment would be useful as a reference for throwing product to the public (consumers). By performing segment of the market will be very helpful introduction to the overall market conditions, how to take advantage of opportunities and understanding of the grouping consumer market segments that can be adjusted with a product that will be marketed through advertising. On that basis in designing advertising must understand and know what is happening in the market as a product toss, so in general, is known there are three criteria that can be used to measure the effectiveness of advertising, namely: sales, admonishment, and persuasion. Keywords: Segmentation, Consumer Behavior, Advertising